A curse on Elizabeth - Stewart, Molly Mia; Pascal, Francine Hu, Ying-Hwa (Bantam Books New York, 1995)
Mrs. Otis's class is going on a field trip to see a special Egyptian exhibit from the tomb of King Ramses XIII. Jessica Wakefield can't wait to look at the pharaoh's jewelry and his gold coffin. But her twin sister, Elizabeth, doesn't want to go. She knows the pharaoh's tomb is cursed